Towards closing the gender gap in Iraq: understanding gender differences in smartphone adoption and use. Issue 4 (2nd October 2019) - Ameen, Nisreen; Willis, Robert
ABSTRACT: This paper examines gender differences in Iraq in terms of smartphone adoption and use, with a specific focus on the factors that can affect women's adoption and use of smartphones. The research used the mobile phone acceptance and use model. In total, 533 questionnaires were distributed to consumers aged 18-29 and the data were analyzed using partial least squares structural equation modelling. The findings revealed that the model fitted well with men and women, but the order of significance of the factors differed between the two genders. Three factors in the model had significantly different effects on behavioral intention when compared by gender. These three factors are culture-specific beliefs and values, habit and perceived relative advantage. The findings indicate that when targeting Iraqi women, other factors in addition to price must be considered.